THE INFLUENCE OF AIR (AUDITORY INTELLECTUAL REPETITION) LEARNING MODEL FOR THE MATHEMATICS LEARNING OUTCOMES - Rizky Fadillah; Suparman Suparman (Universitas Ahmad Dahlan, 2018)
The concept is a crucial thing in learning activities, but the importance is not only in the concept itself, but it depends on how students can understand the concept. The lack of a student's ability to use the concepts for problem-solving causes low student learning outcomes. The purpose of this research to determine the effect of the AIR learning model (Auditory Intellectual Repetition) toward the student learning outcomes in the SMP Negeri 1 Yogyakarta, especially in class VIII and in Even Semester in Academic Year of 2016/2017. The population in this research was the students of class VIII A, VIII B, and VIII C SMP Negeri 1 Yogyakarta in 2016/2017, the total amounted to 103 students. Samples were taken by two classes using the Random Sampling technique for the class, and obtained class VIII B as control class and class VIII C as experiment class. Data collecting techniques used are interview and test methods. The instrument testing uses validity test, normality test, and different power test. The data analysis technique used for the prerequisite test is the normality test with Chi-Square and homogeneity test with the Barlett test formula. As for the hypothesis test using the t-test. The results of this research show that, at a significance level 5%, obtained the conclusion that (1) there is an influence between the results of learning mathematics students using the AIR learning model and students using the STAD learning model. It shows by using the result and thus Â (2) learning by the AIR model can create the result of the learning better than learning by using STAD model. It shows by the result and thus .Â